Inflammatory Measures in Depressed Patients With and Without a History of Adverse Childhood Experiences - de Punder, Karin; Entringer, Sonja; Heim, Christine; Deuter, Christian E.; Otte, Christian; Wingenfeld, Katja; Kuehl, Linn K. (Frontiers in Psychiatry, 2018)
Background: Major depressive disorder (MDD) is a complex psychiatric condition with different subtypes and etiologies. Exposure to adverse childhood experiences (ACE) is an important risk factor for the development of MDD later in life. Evidence suggests that pro-inflammatory processes may convey this risk as both MDD and ACE have been related to increased levels of inflammation. In the present study, we aimed to disentangle the effects of MDD and ACE on inflammation levels. Methods: Markers of inflammation (plasma interleukin(IL)-6 and high sensitive C-reactive protein (hsCRP) concentrations, white blood cell (WBC) count and a composite inflammation score (CIS) combining all three) were assessed in 23 MDD patients with ACE, 23 MDD patients without ACE, 21 healthy participants with ACE and 21 healthy participants without ACE (mean age: 35 ± 11 (SD) years). None of the patients and participants was taking psychotropic medication. ACE was assessed with the Early Trauma Inventory (ETI) and was defined as moderate to severe exposure to sexual or physical abuse. Results: Group differences in the different inflammatory measures were observed. MDD patients with ACE showed significantly higher IL-6 concentrations (p = .018), higher WBC counts (p = .003) and increased general inflammation levels as indicated by the CIS (p = .003) compared to healthy controls. In contrast, MDD patients without ACE displayed similar inflammation levels to the control group (p = .93). Conclusion: We observed elevated inflammation in MDD patients with a history of ACE, which could indicate a subtype of “inflammatory depression”. Accordingly, MDD patients with ACE might potentially benefit from anti-inflammatory therapies.